Imaging Trauma and Polytrauma in Pediatric Patients - Miele, Vittorio; Trinci, Margherita (Springer International Publishing : Imprint: Springer, 2015)
This book provides a detailed and comprehensive overview of the role of diagnostic imaging in the assessment and management of trauma and polytrauma in children. The coverage includes imaging of injuries to the head, thorax, abdomen, bone and musculoskeletal system, with careful attention to the newest imaging techniques, imaging during the course of recovery, and imaging of complications. A series of illustrative cases underline the prognostic value of imaging. In addition, an individual chapter is devoted to diagnostic imaging in cases of child abuse. The book concludes by discussing informed consent and medicolegal issues related to the imaging of pediatric traumatic emergencies. Imaging Trauma and Polytrauma in Pediatric Patients will be invaluable in enabling radiologists and clinicians to identify the main features and signs of injuries on a wide range of imaging techniques, including X-ray, ultrasonography, computed tomography, and magnetic resonance imaging.